Analisis Yuridis Atas Peran Kejaksaan Dalam Optimalisasi Penanganan Tindak Pidana Korupsi di Kabupaten Wajo - Mustari; Martono; Indra Purnama Ramadhan; Gustina (Legal Journal of Law, 2025)
This study aims to determine the legal role of the prosecutor's office in efforts to optimize the handling of corruption in Wajo Regency and to realize the effectiveness of the role of the Prosecutor's Office in eradicating corruption in the region. The method used in this study is a qualitative method with a descriptive-analytical approach, with the object of research in the form of laws and regulations linked to legal theories, as well as the implementation of law in society that is relevant to this study. The results of this study are expected to contribute to knowledge and become a consideration for other researchers who study the role of the prosecutor's office. This study specifically analyzes the legal role of the Prosecutor's Office in optimizing the handling of corruption and identifies steps that can be taken to increase the effectiveness of this role in Wajo Regency. The results of the study indicate that the Wajo District Prosecutor's Office has carried out its legal role optimally through professional and legally based investigation, inquiry, and prosecution functions, and supported by the use of information technology, early detection, and cross-institutional cooperation. To increase the effectiveness of corruption eradication, the Attorney General's Office implements firm law enforcement, provides legal education to the public, provides technical training for prosecutors, and encourages regulatory harmonization between law enforcement agencies. These strategies reflect an approach that focuses not only on enforcement but also on prevention efforts and strengthening a collaborative and integrated legal system.